TEACHING NARRATIVE READING BY USING INTERACTIVE NOTATION SYSTEM FOR EFFECTIVE READING AND THINKING (INSERT) STRATEGY TO THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 2 PRABUMULIH - Ega Vansela (Edukasi, 2016)
The objectives of the study are to find out whether or not there is significant improvement on students’ narrative reading score by using INSERT Strategy to the Eleventh grade students of SMA N 2 Prabumulih, and to find out whether or not there is a significant difference on the eleventh grade students’ narrative reading between those who are taught by using INSERT strategy and those who are not SMA N 2 Prabumulih. This study used quasi-experimental design using nonequivalent pretest-posttest design. The population of this study was the eleventh grades students of SMA N 2 Prabumulih, the sample of this study was class XI MIA 3 and MIA 4 with the total number of students between each class is 31 students. In collecting the data, the test was used. The test was given twice to experimental and control groups, as a pretest and posttest. To verify the hypotheses, the data of pretest and posttest of the experimental and control groups were analyzed by using independent sample t-test and paired sample t-test in SPSS 16 program.  The findings showed that the p-output from paired sample t-test (sig2-tailed)) was 0.000 which was lower than 0.05 and the t-value (12.936) was higher than t-table with df=30 (1.697). P-output from independent sample t-test was 0.000 which was lower than 0.05 and the t-value (5.191) was higher than t-table with df=60 (2.000). It means that teaching narrative reading by using INSERT Strategy had a significant improvement on the students’ narrative reading score.